San Agustín y los sentidos espirituales: el caso de la visión interior - Martin De Blassi, Fernando Gabriel (Teología y vida, 2018)
In the context of a consideration on the God's vision, Augustine of Hippo states in Epistle 147 that the inner eyes are judges of the exterior ones (Cum ergo interior oculi iudices sivi oculorum exteriorum, 17, 41), because the inner eyes see many things that the others do not see, and the corporal perceptions are not judged by carnal eyes. On the contrary, they are judged by the eyes of the heart (oculis cordis). The subject of this disquisition is also raised in Ep. 92, Ep. 148, and Book XXII (ch. 29) of The City of God. Consequently, the present work aims to elucidate the significant notes that St. Augustine develops regarding the inner vision and its superiority with respect to corporeal vision. For the interpretation of the texts, we refer to the instrumental support of sources, along with their corresponding versions in modern languages.